Incidence of obstetric anal sphincter injuries following breech compared to cephalic vaginal births - Perrine Leborne; Renaud de Tayrac; Zakarya Zemmache; Chris Serrand; Pascale Fabbro-Peray; Lucie Allegre; Emmanuelle Vintejoux (BMC, 2023)
Abstract Introduction Obstetric anal sphincter injuries (OASIs) at the time of childbirth can lead to serious consequences including anal incontinence, dyspareunia, pain and rectovaginal fistula. These types of lesions and their incidence have been well studied after cephalic presentation deliveries, but no publications have specifically addressed this issue in the context of vaginal breech delivery. The goal of our study was to evaluate the incidence of OASIs following breech deliveries and compare it with cephalic presentation births. Methods This was a retrospective cohort study involving 670 women. Of these, 224 and 446 had a vaginal birth of a fetus in the breech (breech group) and cephalic (cephalic group) presentations respectively. Both groups were matched for birthweight (± 200 g), date of delivery (± 2 years) and vaginal parity. Main outcome of interest was to evaluate the incidence of OASIs following breech vaginal birth compared to cephalic vaginal births. Secondary endpoints were the incidence of intact perineum or first-degree tear, second-degree perineal tear and rates of episiotomies in each group. Results There was no statistically significant difference in OASIs incidence between the breech and cephalic groups (0.9% vs. 1.1%; RR 0.802 (0.157; 4.101); p = 0.31). There were more episiotomies in the breech group (12.5% vs. 5.4%, p = 0.0012) and the rate of intact or first-degree perineum was similar in both groups (74.1% vs. 75.3%, p = 0.7291). A sub-analysis excluding patients with episiotomy and history of OASIs did not show any statistically significant difference either. Conclusion We did not demonstrate a significant difference in the incidence of obstetric anal sphincter injuries between women who had a breech vaginal birth compared to cephalic.